2017
DOI: 10.3390/v9090262
|View full text |Cite
|
Sign up to set email alerts
|

PERK Signal-Modulated Protein Translation Promotes the Survivability of Dengue 2 Virus-Infected Mosquito Cells and Extends Viral Replication

Abstract: Survival of mosquitoes from dengue virus (DENV) infection is a prerequisite of viral transmission to the host. This study aimed to see how mosquito cells can survive the infection during prosperous replication of the virus. In C6/36 cells, global protein translation was shut down after infection by DENV type 2 (DENV2). However, it returned to a normal level when infected cells were treated with an inhibitor of the protein kinase RNA (PKR)-like ER kinase (PERK) signaling pathway. Based on a 7-Methylguanosine 5′… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 50 publications
3
17
0
Order By: Relevance
“…PCV2 and NDV deploy the PERK pathway for its enhanced replication (29,30). PERK activation contributes to DENV and BTV replication by inducing autophagy and promoting survivability of virusinfected cells (17,31,32). However, PFV infection activates PERK pathway, thereby inducing autophagy, which in turn represses PFV replication (33).…”
Section: Discussionmentioning
confidence: 99%
“…PCV2 and NDV deploy the PERK pathway for its enhanced replication (29,30). PERK activation contributes to DENV and BTV replication by inducing autophagy and promoting survivability of virusinfected cells (17,31,32). However, PFV infection activates PERK pathway, thereby inducing autophagy, which in turn represses PFV replication (33).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, several previous studies have revealed that DENV causes the shutdown of host cell translation activities and in so doing protects cell survival ( Hou et al. 2017 ; Dionicio et al.…”
Section: Discussionmentioning
confidence: 99%
“…It was subsequently transferred onto an Immobilon-P Transfer Membrane (Millipore, Darmstadt, Germany). After blocking with 5% milk-TBS-0.1% Tween 20 buffer at RT for 1 h, the membrane was incubated with the indicated primary and secondary antibodies at RT for 1 h as the method done previously in this lab [ 29 ]. Specific primary antibodies included the 4G2 monoclonal antibody (a kind gift of Dr. Guey-Chuen Perng, National Cheng Kung University, Taiwan) for the dengue E protein and anti-actin mouse monoclonal antibody clone C4 (Merck Millipore, Burlington, MA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Specific strands of viral RNA were then amplified with the primer pair consisting of DV2-N1F (5′-CTGAAACGCGAGAGAA ACCG-3 ′ ) and DV2-N1R (5 ′ -GTATCCCTGCTGTTGG TGGG-3 ′ ). [29]. Specific primary antibodies included the 4G2 monoclonal antibody (a kind gift of Dr. Guey-Chuen Perng, National Cheng Kung University, Taiwan) for the dengue E protein and anti-actin mouse monoclonal antibody clone C4 (Merck Millipore, Burlington, MA, USA).…”
Section: Reverse Transcriptase-polymerase Chain Reaction (Rt-pcr)mentioning
confidence: 99%